Gaining or Losing Team Ball Possession: The Dynamics of Momentum Perception and Strategic Choice in Football Coaches - Briki, Walid; Zoudji, Bachir (Frontiers in Psychology, 2019)
Grounded in the dynamical systems approach, the present research examined the influence of team ball possession (TBP) in soccer on coaches’ perceived psychological momentum (PM) and strategic choice (i.e., game-based “stick” vs. “switch” choices) during a simulated match. Experienced soccer coaches imagined being the coach of the team involved in a highly important match that was displayed on a wall in a lecture hall. The match scenario was manipulated so that the coach was exposed to either a positive momentum sequence (i.e., ascending scenario of TBP) or a negative momentum sequence (i.e., descending scenario of TBP). Results revealed that positive (or negative) momentum sequence increased (or decreased) perceived PM and increased stick (or switch) choices. Perceived PM globally evolved linearly, while strategic choice displayed a dynamical pattern of “critical boundary” (thus showing a nonlinear change). Nonetheless, both variables displayed asymmetrical effects, in the sense that: (a) the strength of positive PM appeared to be easier to decrease than to increase; and (b) the greater the positive PM (or the negative PM) the lesser (or the greater) the coaches’ tendency to make a change in the organization of their teams. This investigation evidences that TBP can powerfully influence coaches’ perceptions and strategic decisions, and that coaches are more likely to be sensitive to negative events and to equivalent positive events.